A method for preparing a diamond copper composite material

By plating the transition layer on the surface of diamond particles and mixing it with copper powder, and using vacuum low-pressure liquid phase sintering technology, the problems of strong pressure and high mold strength in traditional processes are solved, and efficient preparation of large-size diamond copper composite materials and high thermal conductivity material properties are achieved.

CN118581348BActive Publication Date: 2025-04-18赣州金顺科技有限公司 +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411035704.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-31
Publication Date
2025-04-18
Estimated Expiration
2044-07-31

AI Technical Summary

Technical Problem

The pressure required in the traditional vacuum hot pressing sintering process is strong and requires high mold strength, so it is impossible to manufacture large-sized diamond copper composite materials on a large scale.

Method used

By plating the surface of the diamond particles with the transition layer and mechanically mixing it with the copper powder, a uniformly mixed powder was obtained. The diamond copper composite material was prepared at a temperature higher than the melting point of copper or copper alloy by vacuum low pressure liquid sintering process.

Benefits of technology

It effectively reduces the pressure required in the sintering process, reduces the strength requirements for the mold, enables large-sized diamond copper composite materials to be manufactured on a large scale, and improves the density and thermal conductivity of the materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118581348B_ABST
    Figure CN118581348B_ABST
Patent Text Reader

Abstract

The present invention provides a method for preparing a diamond copper composite material. The method comprises the following steps: coating the surface of diamond particles with a transition layer, and mechanically mixing the diamond particles coated with the transition layer with copper powder to obtain a uniformly mixed powder; or mechanically mixing the diamond particles with copper alloy powder to which carbide forming elements are added; loading the uniformly mixed powder into a mold, and performing vacuum low-pressure liquid phase sintering at a preset temperature to prepare the diamond copper composite material. Specifically, since the diamond copper composite material is prepared by vacuum low-pressure liquid phase sintering at a temperature higher than the melting point of copper or copper alloy, the pressure required in the sintering process can be effectively reduced, and the strength requirement of the mold is reduced. In addition, the diamond copper composite material prepared by the method has the advantages of high density and high thermal conductivity, and a special-shaped mold is used to directly manufacture products with complex shapes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of diamond copper composite material preparation, and in particular relates to a method for preparing the diamond copper composite material. Background Art

[0002] With the rapid development of microelectronics technology, electronic devices are moving towards miniaturization and high integration. However, as the performance of the equipment improves, its heat flux density is also increasing. If not effectively managed, it will have a serious impact on the stability, long-term reliability and even the overall performance of the electronic devices. Traditional heat dissipation materials such as metal-based heat sinks can no longer meet the needs of modern electronic devices for efficient heat dissipation. Modern electronic devices not only require heat dissipation materials to have higher thermal conductivity, but also require these materials to be able to function in extremely limited spaces while taking into account lightweight and cost-effectiveness. Therefore, it is urgent to explore and develop new and efficient thermal management materials.

[0003] Diamond is known for its excellent thermal conductivity, with a thermal conductivity of 1000-2200 W / (m·K) and a thermal expansion coefficient of only 2.3×10 -6 K −1 . Diamond / copper composites combine the advantages of diamond's high thermal conductivity and low thermal expansion coefficient, and are expected to become an important material in the field of thermal management. However, copper has a high surface tension, which leads to a relatively large wetting angle between copper and diamond. In addition, since it is difficult for diamond and copper to react chemically, the problem of poor wettability between the two is further increased. From the principle of thermal conductivity, diamond and copper mainly conduct heat in different ways, one by phonon conduction and the other by electron conduction. Ultimately, these factors together lead to the low thermal conductivity of diamond / copper composites. The introduction of an intermediate layer material can achieve a better bond between diamond and copper, effectively reducing the interfacial thermal resistance between them. This intermediate layer can not only promote a closer bond between diamond and copper, but also serve as a bridge for heat transfer, optimize the flow path of thermal energy, and further improve the thermal conductivity of the material.

[0004] At present, the main preparation methods include vacuum hot pressing sintering, spark plasma sintering, high temperature and high pressure sintering, and melt infiltration technology. The core of spark plasma sintering technology is that it not only promotes the bonding between powder particles through instantaneous high temperature discharge, but also significantly improves the sintering efficiency of composite materials. However, the prepared composite materials have a relatively low density, and cannot prepare materials with complex shapes, but can only prepare single sheet materials. High temperature and high pressure sintering is an effective way to prepare high-performance composite materials, especially for those application scenarios that require materials to maintain stability and performance under extreme conditions, but there may be certain limitations in size and shape. The vacuum environment of vacuum hot pressing sintering can effectively reduce the oxidation and other possible chemical reactions of the material during the heating process, thereby maintaining the purity of the material and improving the performance of the final product. At the same time, the applied pressure helps to reduce pores, increase the density of the material, and further improve the mechanical strength and other physical properties of the material. However, this sintering method is not suitable for the preparation of large-size products, and the required mold strength requirements are high, time-consuming, low production efficiency, and high preparation cost. Melt infiltration technology can precisely control the microstructure of the composite material while ensuring material performance, thereby producing diamond composite materials with high thermal conductivity, meeting the stringent requirements of modern industry for high-performance materials. However, the preparation process is relatively complicated, requiring the pre-preparation of diamond blanks, and requiring high-standard configuration of precision molds and sintering equipment. During the reaction, the metal melting, melt flow, and solidification process of the composite material must be under precise control to ensure that the quality and performance of the final product meet the expected standards. Summary of the invention

[0005] Based on this, an embodiment of the present invention provides a method for preparing a diamond copper composite material, which aims to solve the problem that the traditional vacuum hot pressing sintering process requires high pressure, high mold strength requirements, and cannot be mass-produced in large-size diamond copper composite materials.

[0006] The present invention provides a method for preparing a diamond copper composite material, comprising the following steps:

[0007] Mechanically mixing diamond particles coated with a transition layer on the surface with copper powder to obtain a uniformly mixed first powder, wherein the transition layer material is one of molybdenum carbide, tungsten carbide, titanium carbide, zirconium carbide or chromium carbide;

[0008] or mechanically mixing the diamond particles with a copper alloy powder to which one of the carbide-forming elements titanium, zirconium, chromium or boron is added to obtain a uniformly mixed second powder;

[0009] The uniformly mixed powder is loaded into a mold, and when the uniformly mixed powder is the first powder, liquid phase sintering is performed at a temperature higher than the melting point of copper to prepare a diamond copper composite material;

[0010] When the uniformly mixed powder is the second powder, liquid phase sintering is performed at a temperature higher than the melting point of the copper alloy to prepare a diamond copper composite material.

[0011] Furthermore, the temperature is 1085℃~1250℃, the head pressure used in liquid phase sintering is 0.2 MPa~30MPa, and the vacuum degree is 10 -2 Pa ~10 -3 Pa, the holding time is 5min ~ 120 min.

[0012] Furthermore, the size of the diamond particles is 30 μm to 500 μm.

[0013] Furthermore, the coating thickness of the transition layer is 20 nm to 2 μm.

[0014] Furthermore, when the transition layer material is tungsten carbide, the step of coating tungsten carbide on the surface of the diamond particles includes:

[0015] Degreasing and roughening the diamond particles, and mechanically mixing the pretreated diamond particles with tungsten powder to obtain a mixture;

[0016] placing the mixture in a crucible, and uniformly covering the mixture with a mixed salt of NaCl and KCl;

[0017] In an argon atmosphere, tungsten carbide is plated and then cleaned to separate the diamond particles with tungsten carbide plated on the surface.

[0018] Furthermore, the particle size of tungsten powder in the obtained uniform mixed powder is 1 μm to 30 μm.

[0019] Furthermore, in the step of coating tungsten carbide in an argon atmosphere, then cleaning and separating the diamond particles with the surface coated with tungsten carbide, the temperature for coating tungsten carbide is 900° C. to 1150° C., and the holding time is 15 min to 240 min.

[0020] Furthermore, the volume ratio of the diamond particles to the uniformly mixed powder is 20% to 70%.

[0021] Furthermore, the copper powder or the copper alloy powder has a size of 2 μm to 80 μm.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] The diamond particles are coated with a transition layer on their surfaces, and the diamond particles coated with the transition layer are mechanically mixed with copper powder to obtain a uniformly mixed powder, wherein the transition layer is one of molybdenum carbide, tungsten carbide, titanium carbide, zirconium carbide or chromium carbide; or the diamond particles are mechanically mixed with a copper alloy powder to which one of carbide-forming elements titanium, zirconium, chromium or boron is added; the uniformly mixed powder is loaded into a mold, and vacuum low-pressure liquid phase sintering is performed at a preset temperature to prepare a diamond copper composite material. Specifically, since the diamond copper composite material is prepared by vacuum low-pressure liquid phase sintering at a temperature higher than the melting point of copper or copper alloy, the pressure required in the sintering process can be effectively reduced, and the strength requirement for the mold is reduced, so that large-sized diamond copper composite materials can be manufactured on a large scale. In addition, the diamond copper composite material prepared by the method has the advantages of high density and high thermal conductivity, and by using a special-shaped mold, products with complex shapes can be directly manufactured. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 A flow chart of a method for preparing a diamond copper composite material provided by the present invention;

[0025] Figure 2 This is a scanning electron microscope image of the surface metallized diamond particles separated by cleaning in Example 1 of the present invention;

[0026] Figure 3 The XRD spectrum of the surface metallized diamond particles separated by cleaning in Example 1 of the present invention;

[0027] Figure 4 Schematic diagram of the fracture morphology of the diamond-copper composite material in Example 1 of the present invention;

[0028] Figure 5 This is a scanning electron microscope image of the surface metallized diamond particles separated by cleaning in Example 2 of the present invention;

[0029] Figure 6 The XRD spectrum of the surface metallized diamond particles separated by cleaning in Example 2 of the present invention;

[0030] Figure 7 Schematic diagram of the fracture morphology of the diamond-copper composite material in Example 2 of the present invention;

[0031] Figure 8 This is a scanning electron microscope image of the surface metallized diamond particles separated by cleaning in Example 4 of the present invention;

[0032] Fig. 9 is a scanning electron microscope image of the surface metallized diamond particles separated by cleaning in Example 5 of the present invention;

[0033] Fig.10 It is a structural schematic diagram of a graphite mold;

[0034] Fig.11 Schematic diagram of the structure of a diamond copper composite material with a fin heat dissipation array.

[0035] The following specific implementation manner will be further described in conjunction with the above-mentioned drawings. DETAILED DESCRIPTION

[0036] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. Several embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thorough and comprehensive.

[0037] It should be noted that when an element is referred to as being "fixed to" another element, it may be directly on the other element or there may be a central element. When an element is considered to be "connected to" another element, it may be directly connected to the other element or there may be a central element at the same time. The terms "vertical", "horizontal", "left", "right" and similar expressions used herein are for illustrative purposes only.

[0038] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.

[0039] See also Figure 1 , is a flow chart of a method for preparing a diamond copper composite material provided by the present invention, wherein the preparation method specifically comprises the following steps:

[0040] Step S01, mechanically mixing diamond particles coated with a transition layer on the surface with copper powder to obtain a uniformly mixed first powder, or mechanically mixing diamond particles with copper alloy powder added with one of the carbide-forming elements titanium, zirconium, chromium or boron to obtain a uniformly mixed second powder.

[0041] Among them, the transition layer material is one of molybdenum carbide, tungsten carbide, titanium carbide, zirconium carbide or chromium carbide, and the coating thickness of the transition layer is 20 nm ~ 2μm, but the coating thickness of different transition layer materials is different. For example, the coating thickness of tungsten carbide is 100 nm ~ 2μm, the thickness of molybdenum carbide is 50 nm ~ 2μm, and the coating thickness of titanium carbide is 80 nm ~ 2μm.

[0042] Specifically, the process of coating the transition layer on the surface of the diamond particles includes one of a salt bath coating method, a magnetron sputtering method, a vacuum micro-evaporation method or a vacuum diffusion method.

[0043] Specifically, the particle size of the diamond particles is 30μm to 500μm. After the diamond particles are degreased and roughened, that is, pretreated, they are mechanically mixed with the plating raw material, and the mixture is placed in a crucible, and the mixture is evenly covered with a mixed salt of NaCl and KCl. In this embodiment, the plating raw material is tungsten powder. In order to make the tungsten powder fully wrap the diamond particles to achieve uniform plating, the tungsten powder is mechanically mixed with the diamond particles. The final particle size range of the tungsten powder is 1μm to 30μm, but it is not limited to this. In this embodiment, the molar ratio of the mixed salt covering NaCl and KCl is 1:1.

[0044] Furthermore, in an argon atmosphere, tungsten carbide is plated and then cleaned to separate diamond particles with tungsten carbide plated on the surface, that is, surface metallized diamond particles are separated, which can also be understood as surface modified diamond particles. Specifically, the temperature for plating tungsten carbide is 900°C~1150°C and the holding time is 15min~240min. The final tungsten carbide coating thickness is 100 nm~2μm.

[0045] Furthermore, the carbide-coated diamond particles are mechanically mixed with copper powder to obtain a uniformly mixed powder, wherein the size of the copper powder or copper alloy powder is 2 μm to 80 μm, and the volume ratio of the diamond particles to the uniformly mixed powder is 20% to 70%.

[0046] Step S02, loading the uniformly mixed powder into a mold, and when the uniformly mixed powder is the first powder, liquid phase sintering is performed at a temperature higher than the melting point of copper to prepare a diamond copper composite material; when the uniformly mixed powder is the second powder, liquid phase sintering is performed at a temperature higher than the melting point of the copper alloy to prepare a diamond copper composite material.

[0047] It should be noted that the designed mold can be of special shape according to the product appearance requirements, such as the pad can be designed with a groove, etc., wherein the uniformly mixed powder is loaded into the mold, and vacuum low-pressure liquid phase sintering is performed at a temperature higher than the melting point of copper or copper alloy to prepare a high thermal conductivity diamond copper composite material. Specifically, the sintering temperature is 1085℃~1250℃, the pressure head pressure used in liquid phase sintering is 0.2 MPa~30 MPa, and the vacuum degree is 10 -2 Pa ~10 -3 Pa, and the holding time is 5 min~120 min.

[0048] It can be understood that the efficiency of preparing the diamond copper composite material by the embodiment of the present invention is high, and the pressure requirements of the hot pressing equipment and the strength requirements of the mold are low. In addition, compared with the traditional infiltration method, there is no need to prepare the diamond blank in advance. The prepared composite material has high density and thermal conductivity, and can manufacture large-sized high-thermal conductivity diamond copper composite materials. Moreover, this method can directly manufacture products with complex shapes, which is of great significance for realizing large-scale mass production.

[0049] In summary, a method for preparing a diamond copper composite material provided by an embodiment of the present invention comprises the following steps: coating the surface of diamond particles with a transition layer, and mechanically mixing the diamond particles coated with the carbide transition layer with copper powder to obtain a uniformly mixed powder, wherein the transition layer is one of molybdenum carbide, tungsten carbide, titanium carbide, zirconium carbide or chromium carbide; or mechanically mixing the diamond particles with a copper alloy powder to which one of the carbide-forming elements titanium, zirconium, chromium or boron is added; loading the uniformly mixed powder into a mold, and performing vacuum low-pressure liquid phase sintering at a preset temperature to obtain a diamond copper composite material. Specifically, since the diamond copper composite material is prepared by vacuum low-pressure liquid phase sintering at a temperature higher than the melting point of copper or copper alloy, the pressure required in the sintering process can be effectively reduced, and the strength requirement for the mold is reduced, so that large-sized diamond copper composite materials can be manufactured on a large scale. In addition, the diamond copper composite material prepared by the method has the advantages of high density and high thermal conductivity, and by using a special-shaped mold, products with complex shapes can be directly manufactured.

[0050] In order to facilitate understanding of the present invention, several embodiments of the present invention are provided below. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thorough and comprehensive.

[0051] Example 1

[0052] In Example 1 of the present invention, diamond particles with an average particle size of 100 μm and tungsten powder are mixed evenly by ball milling at a molar ratio of 10:1. The tungsten powder particle size ranges from 1 μm to 30 μm in the final mixed uniform powder, and the median particle size D50 is 5 μm. The mixture is placed in a crucible, and a mixed salt of NaCl and KCl with a molar ratio of 1:1 is ground into fine powder with a mortar and evenly spread on the mixed powder. The mixture is treated with a molten salt method in a tubular furnace, heated under an argon atmosphere, kept at 1050°C for 60 minutes, and the heating rate is 5°C / min. Finally, the surface metallized diamond particles are washed and separated, such as Figure 2 and Figure 3 As shown, Figure 2 This is a scanning electron microscope image of the surface metallized diamond particles separated by cleaning in Example 1 of the present invention. Figure 3This is the XRD spectrum of the surface metallized diamond particles separated by cleaning in Example 1 of the present invention.

[0053] The surface modified diamond particles were mixed evenly with copper powder with an average particle size of 38 μm. The mixed powder was placed in a graphite mold and subjected to vacuum low-pressure liquid phase sintering. The sintering conditions were: head pressure 2 MPa, sintering temperature 1120 °C, heating rate up to 10 °C / min, sintering time 15 min, vacuum degree 10 -3 Pa, and then cooled to room temperature, a diamond copper composite material with a size of 100 mm was obtained, and its thermal conductivity was 723 W / (m·K). Figure 4 , is a schematic diagram of the fracture morphology of the diamond-copper composite material in Example 1 of the present invention.

[0054] Example 2

[0055] In Example 2 of the present invention, diamond particles with an average particle size of 100 μm and molybdenum powder are evenly mixed by ball milling at a molar ratio of 10:1. The molybdenum powder particle size ranges from 1 μm to 30 μm in the final mixed uniform powder, and the median particle size D50 is 5 μm. The mixture is placed in a crucible, and a mixed salt of NaCl and KCl with a molar ratio of 1:1 is ground into fine powder with a mortar and evenly spread on the mixed powder. The mixture is treated with a molten salt method in a tubular furnace, heated under an argon atmosphere, kept at 1050°C for 30 minutes, and the heating rate is 5°C / min. Finally, the surface metallized diamond particles are washed and separated, such as Figure 5 and Figure 6 As shown, Figure 5 This is a scanning electron microscope image of the surface metallized diamond particles separated by cleaning in Example 2 of the present invention. Figure 6 This is the XRD spectrum of the surface metallized diamond particles separated by cleaning in Example 2 of the present invention.

[0056] The surface modified diamond particles were mixed evenly with copper powder with an average particle size of 38 μm. The mixed powder was placed in a graphite mold and subjected to vacuum low-pressure liquid phase sintering. The sintering conditions were: head pressure 5 MPa, sintering temperature 1120 °C, heating rate up to 10 °C / min, sintering time 30 min, vacuum degree 10 -3 Pa, and then cooled to room temperature to obtain a diamond copper composite material with a size of 100 mm and a thermal conductivity of 702 W / (m·K). Figure 7 , is a schematic diagram of the fracture morphology of the diamond-copper composite material in Example 2 of the present invention.

[0057] Example 3

[0058] In Example 3 of the present invention, a metal zirconium layer with a thickness of 100 nm is plated on the surface of diamond particles with an average particle size of 200 μm by magnetron sputtering. The surface-modified diamond particles are evenly mixed with copper powder with an average particle size of 10 μm, and the resulting mixed powder is loaded into a graphite mold for vacuum low-pressure liquid phase sintering. The sintering conditions are: a head pressure of 10 MPa, a maximum heating rate of 10 °C / min, a sintering temperature of 1130 °C, a sintering time of 15 min, and a vacuum degree of 10 -3 Pa, and then cooled to room temperature to obtain a diamond copper composite material with a size of 150 mm and a thermal conductivity of 712 W / (m·K).

[0059] Example 4

[0060] Example 4 of the present invention also provides a method for preparing a diamond copper composite material, which differs from Example 1 of the present invention in that the salt bath plating condition is to keep the temperature at 950° C. for 45 minutes. Figure 8 This is a scanning electron microscope image of the surface metallized diamond particles separated by cleaning in Example 4 of the present invention.

[0061] Example 5

[0062] Example 5 of the present invention also provides a method for preparing a diamond copper composite material, which differs from Example 1 of the present invention in that the salt bath plating condition is to keep the temperature at 1100° C. for 45 minutes. Fig. 9 This is a scanning electron microscope image of the surface metallized diamond particles separated by cleaning in Example 5 of the present invention.

[0063] Example 6

[0064] Example 6 of the present invention also provides a method for preparing a diamond-copper composite material, which differs from Example 1 of the present invention in that the sintering temperature is 1085° C. during vacuum low-pressure liquid phase sintering.

[0065] Example 7

[0066] Example 7 of the present invention also provides a method for preparing a diamond-copper composite material, which differs from Example 1 of the present invention in that the sintering temperature is 1160° C. during vacuum low-pressure liquid phase sintering.

[0067] Example 8

[0068] Example 8 of the present invention also provides a method for preparing a diamond-copper composite material, which differs from Example 1 of the present invention in that the sintering temperature is 1200° C. during vacuum low-pressure liquid phase sintering.

[0069] Example 9

[0070] Example 9 of the present invention also provides a method for preparing a diamond-copper composite material, which differs from Example 1 of the present invention in that the sintering temperature is 1250° C. during vacuum low-pressure liquid phase sintering.

[0071] Example 10

[0072] Embodiment 10 of the present invention also provides a method for preparing a diamond-copper composite material, which differs from Embodiment 1 of the present invention in that during vacuum low-pressure liquid phase sintering, the pressure of the pressing head is 0.2 MPa.

[0073] Embodiment 11

[0074] Example 11 of the present invention also provides a method for preparing a diamond-copper composite material, which differs from Example 1 of the present invention in that during vacuum low-pressure liquid phase sintering, the pressure of the pressing head is 0.5 MPa.

[0075] Example 12

[0076] Example 12 of the present invention also provides a method for preparing a diamond-copper composite material, which differs from Example 1 of the present invention in that during vacuum low-pressure liquid phase sintering, the pressure head pressure is 8 MPa.

[0077] Example 13

[0078] Example 13 of the present invention also provides a method for preparing a diamond-copper composite material, which differs from Example 1 of the present invention in that during vacuum low-pressure liquid phase sintering, the pressure of the pressing head is 15 MPa.

[0079] Embodiment 14

[0080] Example 14 of the present invention also provides a method for preparing a diamond-copper composite material, which differs from Example 1 of the present invention in that during vacuum low-pressure liquid phase sintering, the pressure head pressure is 25 MPa.

[0081] Embodiment 15

[0082] Example 15 of the present invention also provides a method for preparing a diamond-copper composite material, which differs from Example 1 of the present invention in that during vacuum low-pressure liquid phase sintering, the pressure head pressure is 30 MPa.

[0083] Example 16

[0084] In Example 16 of the present invention, diamond particles with an average particle size of 100 μm and tungsten powder are mixed uniformly in a molar ratio of 10:1, and the particle size of tungsten powder in the final mixed uniform powder is 1 μm~30 μm. The mixture is placed in a crucible, and a mixed salt of NaCl and KCl with a molar ratio of 1:1 is ground into fine powder with a mortar and evenly spread on the mixed powder. The mixture is treated with a molten salt method in a tubular furnace, heated under an argon atmosphere, kept at 1050°C for 60 minutes, and the heating rate is 5°C / min. Finally, the surface metallized diamond particles are washed and separated.

[0085] The surface modified diamond particles were mixed evenly with copper powder with an average particle size of 45 μm, and the obtained mixed powder was placed in a graphite mold for vacuum low-pressure liquid phase sintering. The graphite mold 2 used had a groove 1 (the groove 1 had a diameter of 5 mm and a depth of 10 mm, such as Fig.10 The sintering conditions are as follows: the pressure of the pressing head is 6 MPa, the heating rate is up to 10 °C / min, the temperature is raised to 400 °C and kept for 60 min, the sintering temperature is 1120 °C, the sintering time is 15 min, and the vacuum degree is 10 -3 Pa, and then cooled to room temperature to obtain a diamond copper composite material with a fin heat dissipation array having a size of 200 mm, including a diamond copper substrate 4 and a diamond copper heat dissipation array 3 (such as Fig.11 As shown in the figure, it is a schematic diagram of the structure of a diamond copper composite material with a fin-type heat dissipation array), and its thermal conductivity is 685 W / (m·K).

[0086] Comparative Example 1

[0087] Using tungsten powder as raw material, tungsten carbide was plated on the surface of diamond particles with an average size of 100um by vacuum diffusion method. The plating conditions were 900℃, 150min, and vacuum degree of 1Pa. The plated diamond particles were evenly mixed with copper powder, loaded into a graphite mold, and hot-pressed sintered at a sintering temperature of 950℃, a pressure of 70MPa, and heat preservation for 60min. The thermal conductivity of the diamond-copper composite material with a diameter of 12.6mm was 562W / (m·K).

[0088] The thermal conductivity test method in Examples 1 to 16 of the present invention and Comparative Example 1 is the laser flash method. The specific results are shown in the following table:

[0089]

[0090] It can be seen from the above table that the diamond copper composite material prepared in the embodiment of the present invention requires lower pressure on the indenter and lower requirements on mold strength than the existing diamond copper composite material. The prepared diamond copper composite material has high thermal conductivity and large size.

[0091] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0092] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a diamond copper composite material, characterized in that: The following steps are involved: Mechanically mixing diamond particles coated with a transition layer on the surface with copper powder to obtain a uniformly mixed powder, wherein the transition layer material is one of molybdenum carbide, tungsten carbide, titanium carbide, zirconium carbide or chromium carbide, and the process of coating the transition layer on the surface of the diamond particles adopts a salt bath plating method; The uniformly mixed powder is loaded into the mold; Liquid phase sintering is performed at a temperature higher than the melting point of copper to prepare a diamond copper composite material; The sintering temperature is 1085℃~1250℃, the head pressure used in liquid phase sintering is 0.2MPa~15MPa, and the vacuum degree is 10 -2 Pa ~10 -3 Pa, holding time is 5min ~ 120 min; The size of the copper powder is 2 μm to 80 μm.

2. The method for preparing the diamond copper composite material according to claim 1, characterized in that: The size of the diamond particles is 30 μm to 500 μm.

3. The method for preparing the diamond copper composite material according to claim 1, characterized in that: The plating thickness of the transition layer is 20 nm to 2 μm.

4. The method for preparing the diamond copper composite material according to claim 1, characterized in that: When the transition layer material is tungsten carbide, the step of coating tungsten carbide on the surface of diamond particles includes: Degreasing and roughening the diamond particles, and mechanically mixing the degreasing and roughening diamond particles with tungsten powder to obtain a mixture; placing the mixture in a crucible, and uniformly covering the mixture with a mixed salt of NaCl and KCl; In an argon atmosphere, tungsten carbide is plated and then cleaned to separate the diamond particles with tungsten carbide plated on the surface.

5. The method for preparing the diamond copper composite material according to claim 4, characterized in that: The particle size of the tungsten powder in the mixture is 1 μm to 30 μm.

6. The method for preparing the diamond copper composite material according to claim 4, characterized in that: In the step of coating tungsten carbide in an argon atmosphere, then cleaning and separating the diamond particles with the surface coated with tungsten carbide, the temperature of coating tungsten carbide is 900° C. to 1150° C., and the holding time is 15 min to 240 min.

7. The method for preparing the diamond copper composite material according to claim 1, characterized in that: The volume ratio of diamond particles to the uniformly mixed powder is 20% to 70%.

Citation Information

Patent Citations

  • Metal based superhard composite and preparation method thereof

    CN105624505A

  • Heat dissipation substrate and preparation method thereof

    CN117020209A